Evolution of flax cell wall ultrastructure and mechanical properties during the retting step. (15th February 2019) - Bourmaud, Alain; Siniscalco, David; Foucat, Loïc; Goudenhooft, Camille; Falourd, Xavier; Pontoire, Bruno; Arnould, Olivier; Beaugrand, Johnny; Baley, Christophe
Highlights: The impact of field retting time was studied on six flax fibres samples. AFM measurements revealed a significant increase of cell wall stiffness with retting. XRD and NMR investigations showed an increase of cellulose crystallinity with retting. NMR evidenced a compaction of inaccessible polymers for most retted sample. This densification can be a possible explanation of the indentation modulus increase. Abstract: Flax retting is a major bioprocess in the cultivation and extraction cycle of flax fibres. The aim of the present study is to improve the understanding of the evolution of fibre properties and ultrastructure caused by this process at the plant cell wall scale. Initially, investigations of the mechanical performances of the flax cell walls by Atomic Force Microscopy (AFM) in Peak Force mode revealed a significant increase (+33%) in the cell wall indentation modulus with retting time. Two complementary structural studies are presented here, namely using X-Ray Diffraction (XRD) and solid state Nuclear Magnetic Resonance (NMR). An estimation of the cellulose crystallinity index by XRD measurements, confirmed by NMR, shows an increase of 8% in crystallinity with retting mainly due to the disappearance of amorphous polymer. In addition, NMR investigations show a compaction of inaccessible cell wall polymers, combined with an increase in the relaxation times of the C4 carbon. This densification provides a structural explanation for the observed improvement in mechanical performance of the secondary wall of flax fibres during the field retting process.